Genetic loci mediating circadian clock output plasticity and crop productivity under barley domestication. Issue 5 (31st March 2021) - Prusty, Manas R.; Bdolach, Eyal; Yamamoto, Eiji; Tiwari, Lalit D.; Silberman, Roi; Doron‐Faigenbaum, Adi; Neyhart, Jeffrey L.; Bonfil, David; Kashkush, Khalil; Pillen, Klaus; Smith, Kevin P.; Fridman, Eyal
Summary: Circadian clock rhythms are shown to be intertwined with crop adaptation. To realize the adaptive value of changes in these rhythms under crop domestication and improvement, there is a need to compare the genetics of clock and yield traits. We compared circadian clock rhythmicity based on Chl leaf fluorescence and transcriptomics among wild ancestors, landraces, and breeding lines of barley under optimal and high temperatures. We conducted a genome scan to identify pleiotropic loci regulating the clock and field phenotypes. We also compared the allelic diversity in wild and cultivated barley to test for selective sweeps. We found significant loss of thermal plasticity in circadian rhythms under domestication. However, transcriptome analysis indicated that this loss was only for output genes and that temperature compensation in the core clock machinery was maintained. Drivers of the circadian clock (DOC) loci were identified via genome‐wide association study. Notably, these loci also modified growth and reproductive outputs in the field. Diversity analysis indicated selective sweep in these pleiotropic DOC loci. These results indicate a selection against thermal clock plasticity under barley domestication and improvement and highlight the importance of identifying genes underlying for understanding the biochemical basis of crop adaptation to changing environments.